The Challenge of Melanocytic Lesions in Pediatric Patients: Clinical-Pathological Findings and the Diagnostic Value of PRAME - Umano, Giuseppina Rosaria; Errico, Maria Elena; D’Onofrio, Vittoria; Delehaye, Giulia; Trotta, Letizia; Spinelli, Claudio; Strambi, Silvia; Franco, Renato; D’Abbronzo, Giuseppe; Ronchi, Andrea; Papparella, Alfonso (Frontiers in Oncology, 2021)
Pediatric melanoma is a rare disease especially in children aged less than 10 years. Recent estimates report a rise of disease incidence in both adults and children. Diagnostic work-up is challenging in pediatric melanoma, as it displays a wide range of clinical presentations. Immunohistochemical biomarkers have been reported as predictors of malignancy in melanoma, however data about pediatric melanoma are poor. Our study aims to contribute to this field of research. We report a retrospective case series of pigmented skin lesions including malignant melanoma, atypical spitzoid tumor, and benign nevi in children and adolescents aged less than 16 years. We described the clinical and demographic characteristics of the cohort and evaluated the immunohistochemical expression of the PReferentially expressed Antigen in MElanoma (PRAME) for differential diagnosis of melanoma in children. The series displayed a similar distribution of melanoma between males and females, and the most common site of melanoma onset were upper and lower limbs. In our cohort, PRAME was not expressed in atypical spitzoid tumor and Spitz nevi. Therefore, immunohistochemical expression of PRAME might be useful in the differential diagnosis of malignant melanoma.